Benefit and Risk of Prolonged Dual Antiplatelet Therapy After Percutaneous Coronary Intervention With Drug-Eluting Stents in Patients With Elevated Lipoprotein(a) Concentrations - Cui, Kongyong; Wang, Hao-Yu; Yin, Dong; Zhu, Chenggang; Song, Weihua; Wang, Hongjian; Jia, Lei; Zhang, Dong; Song, Chenxi; Feng, Lei; Dou, Kefei (Frontiers in Cardiovascular Medicine, 2021)
Background Lipoprotein(a) is positively related to cardiovascular events in patients with coronary artery disease (CAD). Given that lipoprotein(a) has a prothrombotic effect, prolonged dual antiplatelet therapy (DAPT) might have a beneficial effect on reducing ischemic events in patients with elevated lipoprotein(a) levels after percutaneous coronary intervention (PCI). We performed this study to assess the efficacy and safety of prolonged DAPT (>1 year) in this population. Methods We evaluated a total of 3,025 CAD patients with elevated lipoprotein(a) levels who were event-free at 1 year after PCI from the prospective Fuwai PCI Registry, of which 913 received DAPT≤1 year and 2,112 received DAPT>1 year. The primary endpoint was major adverse cardiovascular and cerebrovascular event (MACCE), defined as a composite of all-cause death, myocardial infarction or stroke. Results After a median follow-up of 2.4 years, patients who received DAPT>1 year were associated with lower risks of MACCE compared with DAPT≤1 year (1.6% vs. 3.8%; hazard ratio [HR] 0.383, 95% confidence interval [CI] 0.238 to 0.616), which was primarily driven by the lower all-cause mortality (0.2% vs. 2.3%; HR 0.078, 95% CI 0.027 to 0.227). In addition, DAPT>1 year was also associated with lower risks of cardiac death, and definite/probable stent thrombosis than those who received DAPT≤ 1 year (P < 0.05). Conversely, no difference was found between the two groups in terms of clinically relevant bleeding. Similar results were observed in multivariate Cox regression analysis and inverse probability of treatment weighting analysis. Conclusions In patients with elevated lipoprotein(a) concentrations after PCI, prolonged DAPT (>1 year) reduced ischemic cardiovascular events, including MACCE, all-cause mortality, cardiac mortality, and definite/probable stent thrombosis, without increase in clinically relevant bleeding risk compared with ≤ 1-year DAPT. Lipoprotein(a) levels might be a new important consideration when deciding the duration of DAPT after PCI.